1997
DOI: 10.1055/s-2008-1063938
|View full text |Cite
|
Sign up to set email alerts
|

Nerve Regeneration after Terminolateral Neurorrhaphy: Experimental Study in Rats

Abstract: Four methods of nerve terminolateral neurorrhaphy (TLN) were studied in rat experimental model. In Group A, the distal end of a severed peroneal nerve was sutured end-to-side with an intact tibial nerve trunk, without removal of the tibial epineurium at the suture site. In Group B, the distal end of a severed peroneal nerve was sutured end-to-side with the intact tibial nerve trunk, with removal of the tibial epineurium at the suture site. In Group C, a nerve segment was bridged between the distal part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
9

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 0 publications
4
72
0
9
Order By: Relevance
“…Many authors subsequently confirmed that both sensory and motor nerves had reinnervated recipient nerves through collateral sprouting, through using this technique. [10][11][12] Furthermore, …”
Section: Discussionmentioning
confidence: 99%
“…Many authors subsequently confirmed that both sensory and motor nerves had reinnervated recipient nerves through collateral sprouting, through using this technique. [10][11][12] Furthermore, …”
Section: Discussionmentioning
confidence: 99%
“…51 Accordingly, the number of nerve fibers entering the recipient nerve from the mixed donor nerve was higher after making either an epineurial or perineurial window than after the nerve coaptation with epineurial suturing only, resulting in more effective muscle reinnervation during the first 3 months after end-to-side nerve coaptation. 12,13,29,[48][49][50]54 but not later from 4 up to 8 months after surgery. 16,51,53,64 Interestingly, if epineurial or perineurial windows were enlarged from 1 to 4 or 5 mm, respectively, then, also, the magnitude of axonal ingrowth into the recipient nerve was increased.…”
Section: Kovač Ič Et Almentioning
confidence: 99%
“…This suggests that at least the sprouting sensory axons are able to penetrate the perineurium and epineurium of the donor nerve. 46,47 Creating an epineurial or perineurial window in the donor nerve at the site of end-to-side nerve coaptation with sutures enhanced the sprouting of motor and sensory axons into the recipient nerve in some studies, 12,13,16,29,[48][49][50] but not in others. 35,[51][52][53][54] The effects of either epineurial or perineurial window on the axonal sprouting into the recipient nerve were directly compared in only two studies.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, when there is no injury to the donor nerve, nerve regeneration can occur following endto-side anastomosis, but several experimental studies have shown that when the donor nerve had a fenestration, the effect of nerve regeneration was better [71][72][73][74]. Although there are still controversies over whether fenestration can damage the donor nerve, many studies have confirmed that the fenestration of the epineurium can cause a slight damage to the donor nerve, but does not affect the donor nerve function [75][76][77].…”
Section: Epineurium or Perineurium Windowmentioning
confidence: 99%